Survey: Stock Predictive Models Using Multilayer Perceptron - Rao, A; Hule, S; Shaikh, H; Nirwan, E; Daflapurkar, PM (International Journal of Computer Sciences and Engineering, 2025)
This paper comprehensively surveys the research work in the field of Stock Market Prediction Models that employ Multilayer Perceptron Feed-Forward Artificial Neural Networks. It examines the proposed and/or implemented predictive models by outlining the network configurations of the experimental setups as well as the methodologies utilized to train and improve their prediction accuracies.